Reinforced masonry engineering handbook : clay and concrete masonry - Amrhein, James E. (MIA, CRC, 1998)
This comprehensive handbook encompasses the coefficients, tables, charts, and design data required for the design of reinforced masonry structures. This edition improves and expands upon previous editions, complying with the current Uniform Building Code and paralleling the growth of reinforced masonry engineering. Discussions include materials, strength of masonry assemblies, loads, lateral forces, reinforcing steel, movement joints, waterproofing masonry structures and products, formulas for reinforced masonry design, and retaining walls.